USING PICTURE SERIES IN IMPROVING STUDENTS’ SPEAKING SKILL - Oktaviani Nur Indahsari; Surtiana Harjadijaya; Eva Devi Sofyawati (English Education and Applied Linguistics Journal (EEAL Journal), 2019)
The writer intends to observe the use of picture series to improve the students' speaking ability. The steps are taken purpose to identify the significance of using picture series in improving the students’ speaking ability in a recount text. The study involved one class of the 2nd grade students at SMP Negeri 6 Garut as the sample. The design of this research was pre-experimental and used quantitative method to analyze the problem statement. The writer used pre-test and post-test as the research instrument to find out the result of using picture series in improving students’ speaking ability. The speaking assessment was adopted from Hughes (2002) covering accent, grammar, vocabulary, fluency, and comprehension. The hypothesis of the research is; there is a significant improvement using Picture Series in improving students’ speaking ability in VIIIB class at SMP Negeri 6 Garut. Through the process of experiment with using statistical computation showed that the use of picture series has improved students’ speaking ability significantly in a recount text. Test statistical technique on 0.05 significance level, the results are; that tobserve = 19.622 and tcritical = 2.0423, because tobserve (19.622) is higher than tcritical (2.0423), It meant that there is a significant improving of using picture series in improving students’ speaking skill. In reference to the result of the study, the conclusion was drawn that picture series was successful to improve the students’ speaking ability in recount text. The use of picture series to improve students’ speaking ability was proven effective and significant. By using picture series, students are expected to practice speaking and motivated them to learn speaking. As the suggestion, the use of picture series is recommended to be applied during teaching and learning speaking in junior high schools. It is also important for teachers to select particular pictures appropriate with the students’ needs, interests, and the curriculum as well.